Brookings Papers on Economic Activity 2 / 1995 - Brainard William C; Perry George L (Brookings Institution, 1995)
Plant-Level Adjustment and Aggregate Investment Dynamics, The Transformation of the U.S. Banking Industry: What a Long and Strange Trip It's Been, Currency Crises and Collapses, Stock Ownership Patterns and Stock Market Fluctuations and Consumption, What Do Cross-Country Studies Teach about Government Involvment and Prosperity and Economic Growth?.